Smokers’ and Non-Smokers’ Attitudes towards Smoking Cessation in Saudi Arabia: A Systematic Review - Tobaiqy, Mansour (Int J Environ Res Public Health, 2020)
Literature on smoking in Saudi Arabia is extensive. However, studies capturing the attitudes of both smokers and non-smokers towards smoking cessation are few. A PRISMA-P protocol guided systematic searches in MEDLINE and CINAHL on MeSH terms (smoking cessation AND Saudi Arabia). Peer reviewed articles in English were included in the narrative analysis. Screening reduced the 152 articles identified to 15 and independent critical appraisal identified 10 final articles for review. Few adopted validated survey tools or mentioned the best practice to be followed. There was considerable variation in the prevalence of smoking reported (13.7–49.2%) and survey response rates (8.9–100%). There was a paucity of quality evidence but it is clear that the smoking pandemic is still resonant in Saudi Arabia. Despite support for education programs to prevent the uptake of smoking, policy-driven action to reduce environmental second-hand smoking, and provision of support for smoking cessation, more needs to be done.